The Role of Digital Promotion in Increasing Participation in Islamic Boarding School Programs - Maskuri Abdul Rohman; Muhammad Sirodjuddin; Muhammad Ridlwan (Journal of Social Studies and Education, 2025)
The main focus of this study is to analyze the role of social media, especially Instagram and Facebook, in attracting the attention of parents and participants, as well as the program's effectiveness in creating an emotional attachment that encourages participants to continue their education to regular programs. The research method used is a qualitative approach with in-depth interview techniques involving the head of the pesantren and several program participants. The study results show that the optimal use of social media has increased the number of participants by up to 158 people compared to the previous year. In addition, the holiday cottage program has also proven to be effective in building participant satisfaction, which is reflected in more than 50 participants who expressed their satisfaction and desire to continue the program to a regular level. This program has also successfully introduced pesantren values in a more attractive and relevant way for the younger generation. The implications of these findings show that digital promotion strategies, which combine social media and participant testimonials, can increase the attractiveness of pesantren as a modern educational option but still based on religious values. The study also suggests the importance of integrating religious learning and developing social and leadership skills to respond to the demands of modern education.